Cardiotoxicity related to intrapericardial infusion of bevacizumab in the treatment of lung cancer-mediated malignant pericardial effusion: a case report - Wu, Shilong; Lu, Yanjun; Xu, Chenyang; Liu, Huafeng (Frontiers in Pharmacology, 2025)
BackgroundLung cancer can result in malignant pericardial effusion (MPE), impacting patient prognosis. Intrapericardial infusion of bevacizumab was an alternative treatment for MPE.Case presentationWe present the case of a 48-year-old female with stage IV lung adenocarcinoma and MPE. MPE was managed by intrapericardial infusion of bevacizumab. The first intrapericardial infusion of bevacizumab effectively controlled the MPE for 8 months. Cardiotoxicity quickly emerged after the second intrapericardial infusion of bevacizumab. After intensive treatment, the symptoms of cardiotoxicity resolved within 10 days.ConclusionThe present case indicates that intrapericardial infusion of bevacizumab could lead to cardiotoxicity in MPE patient. Cardiac examinations should be conducted before and after anti-vascular endothelial growth factor treatment.